Rudolf Hoess ‒ Chief Commandant of the Auschwitz Concentration Camp (Archives of Criminology, 2004)
This article has been published in 1951 in the Bulletin of rhe Main Commission for the Investigation of the Hitler Crimes in Poland. After 60 years past the end of the Second World War, we have decided to republish it, driven by a belief that its content - presentation of Hoess’ personality uncovered in criminology studies, as well as the mechanisms behind his rise to becoming one of the biggest war criminals ever, deserves another reminder in the contemporary times.        The article has been prepared based on long hours of life investigation on the person of Rudolf Hoess by prof. Batawia in a Warsaw prison, and also on an auto-biography of Hoess - an important historical document. Prof. Batawia presents Hoess’ personality in connection with historical processes of the epoque, with Hitler’s fascism, with social conditions that Hoess lived in.        In the introduction there is a brief presentation of documents with the goals and plans of Hitler’s imperialism - conquering Europe, the exploitation of the labour force in different countries, systematic biological destruction of the nations, conquered the mass human extermination of the ‘lower’ races and nations. There is a short description of the biggest concentration camp in Auschwitz where merciless exploitation of the labour force was a daily occurrence, where hundreds of thousands of prisoners were exterminated also with at least 250 000 Jewish people who cannot be called prisoners for straight after their arrival they were directed to gas chambers.        Who was the chief commandant of the Auschwitz camp - the place of suffering and death of millions of people from all over Europe?        This work is an attempt to answer that question examining his family environment and his life experiences.        His father was a German army officer raising his son in a rigorous atmosphere of strict moral rules, religious fanatism, in unconditional respect for adults whose opinions Hoess treated as mostly righteous and absolutely certain. Rudolf Hoess was a hard working and obedient student, yet his school results were average, he read little, too. During the First World War he wanted to join the army but he was too young; he helped in an army hospital where he had difficulties coping with human hurt and with the dieing of the wounded, yet with time he began getting used to it. At the age of 16 he was an exemplary German soldier, left under spell of the soldierly customs, the tough army discipline, he listened to all orders and was absolutely obedient to his supreme officers. At the age of 17 he was the youngest non-commissioned officer awarded First Class Iron Cross. After the cease-fire he signed up for the Voluntary Baltic Corps in Królewiec, a strongly right wing, nationalistic army organisation. It was made up of ex-army soldiers, who could not accept Germany’s loss of the war, the new situation within their country, unemployed people, declassed and pauperised as well as of simple trouble makers. The corps were managed by extremely nationalistic circles, the Junkers and the Military, revenge and terror against political enemies were their ideology. Hoess considered it a patriotic military organisation, defending arm’s honour after the war defeat and building bases for new powerful Germany. He was uncritical of his supervisors’ believes and considered them the only truthful ones. This was his preparation by the precursors of Hitlerism to take up the NSDAP ideology, which he joined 1922 recognising Hitler’s programme as attractive in the contemporary situation of Germany. In 1923 he was sentenced for 10 years of imprisonment for participation in murder of an ex-member of the Corps, sentenced to death by the vehmgericht for treachery. He spent 6 years in prison, he was an exemplary prisoner, unconditionally obedient, thoroughly fulfilling all of his prison duties, who believed it was deeply immoral to behave the way his fellow criminal prisoners did. He read a lot while in captivity, mostly books sent by his friends about the national-socialist ideology. He was released in amnesty and left political activity, settling in a tranquillity of a countryside and working as a farmer. Approving of the NSDAP ideology he condemned the brutality and immoral level of the methods used there and of its many members. After 3 years of managing a farm where he worked, he was offered a job of organising a horse squad of SS, which he accepted immediately, seeing in SS, as he claimed, only soldiers, eminent in their faithfulness to the party ideology. This decision came with his general admission to the SS, and next with a hesitant decision to enter the active SS after Himmler’s offer. He was trained in the concentration camp in Dachau. It was not at all different to a regular training. The trainees were taught certain types of stereotypical behaviours, reacting in an changeable, standard way with a suppression of criticism towards particular stimuli and own reactions. Certain words, symbols were to create a ready made, involuntary reactions. Methods used in such training were to weaken one’s critical thinking, higher emotions, and ability to control aggressive tendencies by means of ethical values. These methods aimed at dehumanising a human being, turning it into an individual with a harmed psyche. The very anti-rational ideology of nationalist-socialists favoured a diminishing of intellect. The SS were prepared to obey orders blindly, especially those of Fuhrer, whose person ind rightness they were taught to believe in uncritically. The primary role was played by the apotheosis of hatred and killing in oneself any compassion for the enemy. The training aimed at familiarising the SS men with cruelty and prepared them for active participation in acts of aggression. That also concerned Hoess who, as he claimed, under a mask of indifference controlled his compassionate feelings for cruelly treated prisoners. He also applied for being moved to the army formation, which he was eventually refused. After several years of serving in the Dachau concentration camp he was moved to another camp in Sachsenhausen where he was promoted to vice-commandant. In 1940 he was made responsible for organising a concentration camp in Auschwitz where he was finally made a commandant.        He never doubted the point and rightness of concentration camps, believing that the enemies of the IIIrd Reich should be isolated and that all orders should always be obeyed. He treated extremely seriously the task he was given and he put a lot of effort to be an exemplary SS man. He believed deeply and unconditionally in the nationalist-socialist ideology. However, he never, as he admitted, hated the prisoners, the Jews, the Communists, or the political criminals, he regarded them as enemies who, for the better good, should be put out of action. He wished to make Auschwitz an exemplary concentration camp, to make it the best at accomplishing the economic tasks during the war time. From the very beginning, in his own words, he faced severe obstacles, he was sent the worst kind of SS soldiers, he was prevented from creating better conditions for the prisoners. He did not understand that the central government was aiming at such very extermination of the peoples inhabiting the occupied countries. He did see the masses of dead corpses, he was aware of the numerous incidents of tortured prisoners, but having no personal contact with them he thought of them as a mass, on top of that he was powerless while his interventions were without effects. Why didn’t he resign observing the turning of a concentration camp into an extermination camp? He considered that strange to an SS man’s behaviour. The order of the ‘Final Solution’ of the Jewish question was in his opinion horrifying, but being it a Hitler’s order - no one had the right to question it. When directing the exiermination action, looking at gas killings of women and children he felt, as he claimed, fear, objection and disgust, yet it was not a compassion, for it is difficult to feel compassion towards a mass. He admitted to having directed an extermination action of 1 200 000 Jews from all over Europe.        2nd of April 1947 Rudolf Hoess was sentenced to death by the Highest National Tribunal in Warsaw.       The life of the commandant of the Auschwitz concentration camp shows that he was not an abnormal individual, emotions free, with sadistic tendencies. It reveals he was a man of average intelligence, little critical, easily submitting to any authority. He was an introvert, used to a very serious attitude towards his own duties which he fulfilled with extreme thoroughness and passion. These qualities of his, have been well utilised by Hitlerism. We can clearly observe a metamorphosis of once socially harmless individual into a kind of fascist mentality, into a criminal of rarely met dimension. His story shows that fascist ideology can push into the tracks of major cruelty even those individuals who might seem far from brutal or cruel. That a fascist ideology can turn people personally incapable of harming victims, into war criminals of incomparable dimension. The truth about very significant reasons behind the tragic events of that time emerges, as well as a warning for the future.